2008
DOI: 10.1103/physrevc.77.014313
|View full text |Cite
|
Sign up to set email alerts
|

β decay of neutron-richCa5356

Abstract: β-decay properties of neutron-rich Ca isotopes have been obtained. Half-life values were determined for the first time for 54 Ca (86 ± 7 ms), 55 Ca (22 ± 2 ms), and 56 Ca (11 ± 2 ms). The half-life of 230 ± 60 ms deduced for 53 Ca is significantly longer than reported previously, where the decay chain 53 K → 53 Ca → 53 Sc was considered. A delayed γ ray with energy 247 keV was identified following β decay of 54 Ca, and is proposed to depopulate the 1 + 1 level in 54 Sc. The β-decay properties compare favorably… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
51
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 53 publications
11
51
0
Order By: Relevance
“…Recently, it was shown that the beta-decay half-lives of the neutron-rich Ca isotopes [25] compare favorably with the results of shell-model calculations performed in the full pf model space using the GXPF1 effective interaction [26]. The systematic trend of these half-lives is consistent with the presence of a subshell gap at N = 32 as predicted by this interaction and confirmed by a variety of experiments.…”
Section: Fig 1 (Color Online)supporting
confidence: 67%
See 2 more Smart Citations
“…Recently, it was shown that the beta-decay half-lives of the neutron-rich Ca isotopes [25] compare favorably with the results of shell-model calculations performed in the full pf model space using the GXPF1 effective interaction [26]. The systematic trend of these half-lives is consistent with the presence of a subshell gap at N = 32 as predicted by this interaction and confirmed by a variety of experiments.…”
Section: Fig 1 (Color Online)supporting
confidence: 67%
“…A similar trend had already been pointed out by Mantica et al [25] where they deduce that the effective energy gap between the adjacent neutron single-particle orbitals f 5/2 and p 1/2 is overestimated by the GXPF1 and GXPF1A effective interactions. Based on this, the GXPF1B interaction has been modified to correct this 0.5 MeV shift and is referred to as GXPF1B5 here.…”
Section: Fig 1 (Color Online)supporting
confidence: 57%
See 1 more Smart Citation
“…''This work gives evidence for three new K and Ca isotopes and provides further information on half-lives and P n values''. The measured half-life of 90(15) ms is somewhat smaller than the recent measurement of 230(60) ms [30]. Mantica et al analyzed their data with both half-life values and found the fit for the longer half-life slightly better based on the R 2 regression analysis.…”
Section: Camentioning
confidence: 93%
“…Mantica et al analyzed their data with both half-life values and found the fit for the longer half-life slightly better based on the R 2 regression analysis. In addition, the authors mentioned that a second β-decaying state could have contributed to the longer half-life value [30]. [54][55][56] Ca 54 Ca, 55 Ca, and 56 Ca were first observed by Bernas et al in 1997, reported in ''Discovery and cross-section measurement of 58 new fission products in projectile fission of 750.A MeV 238 U'' [31].…”
Section: Camentioning
confidence: 95%